Mengembangkan Koperasi Sebagai Pemberdaya Ekonomi Rakyat Indonesia - Mulyono, Fransisca (Jurnal Administrasi Bisnis, 2010)
Cooperative in Indonesia is an mandated institution as mentioned in Undang-undangDasar 1945. After 65 years in its development, cooperatives in Indonesia is stillnot developing well. In other countries cooperatives proved to become successfulbusiness organizations. This paper aimed to describe and analyze the causes ofunderdevelopment of cooperatives in Indonesia.Keywords: Traditional market, cooperation, professionalism of cooperation